To create a modern agriculture : organization and planning - Mosher, Arthur Theodore (New York, Agricultural Development Council, 1971)
This book, based on three Lectures delivered at the Indian Agricultural Research Institute, New Delhi in February 1971 considers that most countries in South and Southeast Asia are now in a position where they could create a modern agriculture fairly quickly, at least in some parts of each country, but that patterns of organization of public agricultural activities and planning methods adopted have been inappropriate to the task. Implications with respect to agricultural planning are listed as: (1) Planning to create a modern agriculture must include attention to both technological and institutional change. (2) Planning should embrace all public activities related to agriculture: production, growth and adjustment. (3) Effective agricultural planning requires an appropriate specification of the " activities " among which resources are to be allocated. (4) Sound allocative planning for agriculture requires disaggregation of certain activities in accord with the varying current agricultural growth potential of different parts of the country. (5) Agricultural planning should utilize sequences, gestation periods and complementarities as criteria in making allocations, rather than separately estimated rates of return. (6) Planning should focus on systematically building the structure of a modern agriculture. (7) Those who participate in agricultural planning must understand the nature of agriculture and the process of agricultural growth.
Includes bibliographies.
occ 17/01/2019
Loans
Keywords: Agriculture and state; Modern agriculture; Agricultural planning